2007
DOI: 10.4049/jimmunol.178.2.732
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Counteracts the Regulatory T Cell-Mediated Suppression of Human CD4+ T Lymphocytes

Abstract: High expression of IL-21 and/or IL-21R has been described in T cell-mediated inflammatory diseases characterized by defects of counterregulatory mechanisms. CD4+CD25+ regulatory T cells (Treg) are a T cell subset involved in the control of the immune responses. A diminished ability of these cells to inhibit T cell activation has been documented in immune-inflammatory diseases, raising the possibility that inflammatory stimuli can block the regulatory properties of Treg. We therefore examined whether IL-21 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
210
3
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(229 citation statements)
references
References 27 publications
14
210
3
2
Order By: Relevance
“…IL-21 made a particularly attractive candidate for driving the difference, given its overexpression in NOD Tconv cells and its growth-enhancing properties (33). In addition, Peluso et al reported that IL-21 renders human CD4 ϩ CD25 Ϫ T cells refractory to in vitro suppression (34). IL21 maps to the idd3 diabetes-susceptibility region, and we confirmed that the higher IL-21 expression in NOD Tconv cells (23,30,31) was indeed a function of that locus, as NOD.idd3 b/b congenic mice exhibited the same low level of IL-21 transcripts as did B6g7 mice according to reverse transcriptase-polymerase chain reaction (RT-PCR) quantification (data not shown).…”
Section: Conventional T Cells ͉ Regulatory T Cells ͉ Type 1 Diabetesmentioning
confidence: 99%
“…IL-21 made a particularly attractive candidate for driving the difference, given its overexpression in NOD Tconv cells and its growth-enhancing properties (33). In addition, Peluso et al reported that IL-21 renders human CD4 ϩ CD25 Ϫ T cells refractory to in vitro suppression (34). IL21 maps to the idd3 diabetes-susceptibility region, and we confirmed that the higher IL-21 expression in NOD Tconv cells (23,30,31) was indeed a function of that locus, as NOD.idd3 b/b congenic mice exhibited the same low level of IL-21 transcripts as did B6g7 mice according to reverse transcriptase-polymerase chain reaction (RT-PCR) quantification (data not shown).…”
Section: Conventional T Cells ͉ Regulatory T Cells ͉ Type 1 Diabetesmentioning
confidence: 99%
“…A further manner in which IL-21 may contribute to autoimmunity is by imparting resistance to T reg suppression. Several investigators have shown that IL-21 is able to counteract the suppressive function of T reg [77,87] and that this requires the IL-21 to act on conventional CD4 T cells [85,88], rather than the T reg themselves. Interestingly, resistance to T reg suppression has been reported in both mice [77] and humans with T1D [89,90], although many other factors in addition to IL-21 are likely to contribute to this effect [91].…”
Section: Possible Roles For Il-21 In Autoimmune Diabetesmentioning
confidence: 99%
“…For example, IL-21 induces the production of tissue-degrading matrix metalloproteinases from intestinal fibroblasts, 56 stimulates the synthesis of the T-cell chemoattractant macrophage inflammatory protein-3a (MIP-3a)/CCL20 from colonic epithelial cells, 57 renders CD25 ) CD4 + T cells resistant to Treg-mediated suppression, 58,59 and in some cases enhances IFN-c production from T cells and natural killer (NK) cells 60,61 (Table 2). Moreover, T-cell-derived IL-21 is thought to act in an autocrine fashion to induce Th17 cells.…”
Section: Interleukin-23 Has Broad Effects On Both T Cells and Non-t Cmentioning
confidence: 99%